(untitled) (Journal of Organizational Psychology, 2021)
Telecommuting is a growing trend among the American workplace (Gallup, 2017, Kopf, 2018, Kossek et al., 2006, Lucas, 2018). While telecommuting has been shown to have numerous benefits, lack of formal policies regarding telecommuting and uniform treatment of on-site and off-site workers, can lead to unintended consequences for organizations, such as jealousy and resentment of remote workers by those who do not telecommute (Allen et al., 2015, Crandall et al., 2005, Golden, 2007, Lucas, 2018). Two potential sources of this discontent are companies’ sick leave and vacation time policies. This article discusses issues that can originate because of these policies and potential solutions to reduce the perceived disparity in fairness between remote and on-site workers with regard to sick leave and vacation time.